CULTIVATION AND BIOECOLOGICAL CHARACTERISTICS OF THE MEDICINAL HYSOP (HYSOPPUS OFFICINALIS L.) PLANT (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article describes the cultivation technology, biology, ecology, importance of the medicinal hyssop plant (hysoppus officinalis L.) in agriculture and national economy, chemical composition and medicinal properties.